ELECTRONIC-STRUCTURE OF THE IDEAL VACANCIES IN (HG, CD)TE - (:unkn) unknown (AKADEMIE VERLAG GMBH, 1991)
The localized orbital method (LOM) based upon an atomic-like basis set and empirical pseudopotential Hamiltonian in conjunction with the Green's function method is employed for the study of electron states of ideal vacancies in (Hg, Cd)Te. This method is used for the first time for a calculation of ideal vacancies in (Hg, Cd)Te. Bloch sums are formed from Gaussian orbitals of s and p symmetry on each atomic site. A systematic study shows that an accurate description of band energies and density of states can be obtained, with the use of a minimal Gaussian set. Since the relativistic terms are neglected the weighted average of the spin splitted levels of HgTe and CdTe are used for the calculation of band energies and densities of states. The calculated ideal vacancy states are in general agreement with what is known about defect levels in (Hg, Cd)Te.
Keywords: LOCALIZED-ORBITAL DESCRIPTION; BAND STRUCTURES; WAVE-FUNCTIONS; SEMICONDUCTORS; STATES; DEFECTS; SILICON; DENSITY; ALLOY